2011
DOI: 10.1097/ta.0b013e3181f30fc9
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Splenectomy Decreases Mortality and Improves Cognitive Function of Rats After Severe Traumatic Brain Injury

Abstract: Our study demonstrates that splenectomy has a protective effect on rats with severe TBI by inhibiting proinflammatory cytokines, including IL-1β, TNF-α, and IL-6, both systematically and locally in the injured brain, hence leading to a decreased mortality and improved cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 23 publications
7
55
0
Order By: Relevance
“…3 B, G). The magnitude of these changes is similar to those previously reported using CCI and weight-drop models (Li et al, 2011;Shein et al, 2014), and are comparable to the levels seen in human TBI patients. For example, we observed that CCI resulted in a mean plasma concentration of IL-6 of 90 pg/ml when assessed 6 h after injury.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…3 B, G). The magnitude of these changes is similar to those previously reported using CCI and weight-drop models (Li et al, 2011;Shein et al, 2014), and are comparable to the levels seen in human TBI patients. For example, we observed that CCI resulted in a mean plasma concentration of IL-6 of 90 pg/ml when assessed 6 h after injury.…”
Section: Discussionsupporting
confidence: 77%
“…The vagus nerve is a key participant in the communication between the brain and components of the immune system, playing an important role in the regulation of peripheral inflammation. Consistent with this, vagus nerve stimulation has been demonstrated to decrease inflammation in models of sepsis and arthritis Kox et al, 2015). For TBI, a brief 10 min stimulation of the vagus nerve immediately before experimental brain injury has been reported to decrease BBB permeability assessed 6 h later (Lopez et al, 2012).…”
Section: Discussionmentioning
confidence: 55%
“…53 Other data suggest that splenectomy prevents IRI in rats 54 and the spleen plays a deleterious role in animal models of stroke. 55,56 These studies portray the spleen as a source of proinflammatory cells that propagate ischemic tissue injury. By contrast, results from our study (showing that prior splenectomy did not reduce the development of IRI) and others 57 reveal a beneficial, anti-inflammatory role of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Splenectomy has also proven to be beneficial in other types of brain injuries, such as hemorrhagic stroke and traumatic brain injury. [11][12][13][14] In fact, the splenic response to ischemic injury occurs in organs throughout the body. Researchers in the field of liver injury were among the first to report that removal of the spleen before ischemia reperfusion injury to liver is hepatoprotective.…”
Section: Introductionmentioning
confidence: 99%